2022
DOI: 10.1101/2022.03.23.485369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Signal and Measurement Considerations for Human Translation of Diffuse in vivo Flow Cytometry

Abstract: SignificanceDiffuse in vivo flow cytometry (DiFC) is an emerging technology for fluorescence detection of rare circulating cells directly in large deep-seated blood vessels in mice. Because DiFC uses highly scattered light, in principle it could be translated to human use. However, an open question is whether fluorescent signals from single cells would be detectable in human-scale anatomies.AimSuitable blood vessels in a human wrist or forearm are at a depth of approximately 2-4 mm. The aim of this work was to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In addition to the advantages of NIR-DiFC described above, as summarized in fig. 4 we observed that tissue autofluorescence is markedly reduced and the signal is free of motion artifacts (35) compared to our pre-clinical GFP-compatible b-DiFC instrument (31). Use of blue laser light is widely understood to yield higher biological tissue autofluorescence than near-infrared light (49).…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…In addition to the advantages of NIR-DiFC described above, as summarized in fig. 4 we observed that tissue autofluorescence is markedly reduced and the signal is free of motion artifacts (35) compared to our pre-clinical GFP-compatible b-DiFC instrument (31). Use of blue laser light is widely understood to yield higher biological tissue autofluorescence than near-infrared light (49).…”
Section: Resultsmentioning
confidence: 72%
“…We first tested NIR-DiFC using an optical flow phantom ( Fig. 2a ), which we have shown previously approximates the optical properties of bulk biological tissue in the NIR range (35). Peaks were never observed in control solutions of either PBS or unlabeled cells; a representative NIR-DiFC data scan for unlabeled L1210A cells is shown in fig 2b .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations